Analysis of CSR Program Disclosures in Sustainability Reports Based on GRI Standard and AA1000 - Dewi Djumiyati; Agus Munandar (Penerbit Goodwood, 2026)
Purpose: This study examines the disclosure of CSR programs in the sustainability reports of banking companies included in the KBMI 4 category. Methodology/approach: Qualitative analysis with descriptive analysis. Results/findings: The analysis shows that the level of hunger disturbance based on the GRI Standards for banks in KBMI 4, has shown significant progress during the 2022-2024 period. All four banks consistently implemented the requirements in accordance with POJK No. 51/POJK.03/2017, with a high level of compliance with the general standards and accountability principles of AA1000, although there are still variations in disclosures of standard topics. Conclusions: The sustainability report disclosure of KBMI 4 banks showed significant progress during 2022-2024. All four consistently complied to with POJK No. 51/POJK.03/2017 and AA1000 accountability principles, with generally high adherence to GRI Standard. Despite variations in topic disclosures, CSR reporting has become a key strategy to enhance image, public trust, and sustainable competitiveness. Limitations: The scope of the study was limited to banks in KBMI 4, observation period only covered 2022-2024, focused on CSR disclosure and research data is secondary in nature. Contributions: The Banks within KBMI 4 have implemented CSR programs to support sustainability in accordance with applicable standards and support sustainable development in Indonesia.